A method for preparing ultra-lightweight, high-strength and energy-saving building blocks
By using chemical foaming agents of aluminum powder and ferrosilicon alloy powder and physical foaming agents of protein foaming liquid in autoclaved aerated concrete, a uniform pore structure is formed, and the problem of single pore size and pore distribution in the prior art is solved, and the stable production and performance improvement of lightweight and high-strength blocks are achieved.
Patent Information
- Application Number
- CN202411989254.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The pore size and pore distribution of existing autoclaved aerated concrete products are single, which restricts the stable production of lightweight and high-strength blocks. The preparation process is complex and the use efficiency of aerator is low, which limits mass production.
Aluminum powder and ferrosilicon alloy powder are used as chemical foaming agents for chemical foaming, and combined with the physical foaming agent protein foaming solution to form a dense and uniform pore structure, improving the strength and thermal conductivity of concrete blocks.
It realizes the lightweight and high-strength properties of concrete blocks, improves stability, thermal conductivity, frost resistance and mechanical properties, and meets the requirements of continuous production.
Smart Images

Figure CN119775047A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to a method for preparing an ultra-lightweight, high-strength, energy-saving building block. Background Art
[0002] At present, the demand for the development of green buildings, building materials and prefabricated buildings is becoming stronger and stronger. Green building materials marked by environmental protection have become the key object to promote the development of the construction industry. Aerated concrete has attracted much attention from the construction industry due to its light weight, strong thermal insulation performance, good fireproof effect and the ability to process products of different sizes. It has become a new type of green building material that is rapidly promoted and developed in most countries and is widely used in masonry structures and frame structures of industrial and civil buildings. Compared with traditional building materials such as sintered bricks, aerated concrete blocks can reduce the waste of resources and reduce environmental pollution, and can also accelerate the development of my country's construction industry.
[0003] Aerated concrete itself is a porous material that achieves the effect of lightweight insulation by introducing a large number of pores, and the pore structure itself determines the macroscopic properties of aerated concrete. In the field of concrete, air-entraining agents can introduce a large number of small bubbles, which can cut off the capillary passages and reduce the capillary action, thereby improving the impermeability of concrete. The micropores formed by these small bubbles can also release the ice crystal expansion pressure in the capillary during the freezing process of concrete, reduce and prevent freeze-thaw damage, and significantly improve the frost resistance of concrete.
[0004] At present, the gas generation method of autoclaved aerated concrete is mainly chemical foaming, among which aluminum powder has become its first choice as a foaming agent. However, lightweight and high-strength self-insulating blocks have become the mainstream development of autoclaved aerated concrete in the future. The single aluminum powder foaming makes the pore size and roundness of aerated concrete products relatively simple, and the pore distribution is concentrated in a certain range, which restricts the stable production of lightweight and high-strength blocks. In addition, the preparation process of autoclaved aerated concrete is complicated, the chemical foaming environment requirements are harsh, and the thickening rate of the slurry and the gas generation rate of the gas generating agent are difficult to effectively control, resulting in low efficiency of the use of the gas generating agent, a large number of merged pores and connected pores in the pore structure, which limits the mass production of lightweight and high-strength blocks. Summary of the invention
[0005] In order to solve the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing ultra-lightweight, high-strength and energy-saving building blocks. The present invention uses aluminum powder and ferrosilicon alloy powder as chemical foaming agents for chemical foaming, and then combines physical foaming agent protein foaming liquid to make the internal pore structure of the concrete dense and uniform, so that the product lightweight and high-strength concrete blocks have good stability, thermal conductivity, antifreeze performance, compressive strength and mechanical properties, which can meet the requirements of continuous production.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A method for preparing an ultra-lightweight, high-strength, energy-saving building block, the method comprising the following steps:
[0008] (1) Slurry preparation: The weighed fly ash is made into fly ash slurry with a certain water content, and the fly ash slurry is stored in a slurry tank for standby use;
[0009] (2) Mixing and pouring: Cement, gypsum and ground lime are weighed from the respective silo tanks, mixed evenly with the weighed admixture slurry, the fly ash slurry obtained in step (1) and the physical foaming agent, and then the weighed chemical foaming agent is added, mixed evenly and poured into a mold;
[0010] (3) Curing: The mold cast in step (2) is transferred to a curing room with a certain temperature and humidity for curing to ensure that the slurry completes the thickening and hardening process normally;
[0011] (4) Cutting: After the resting stage, the slurry will harden to form a green body. When the green body reaches a certain strength, it is flipped 90 degrees by a flip hanger and lifted to a cutting machine to cut the green body according to the designed size;
[0012] (5) Autoclave curing: The green bodies cut in step (4) are hoisted by a loading crane onto a steam curing trolley for stacking and assembly, and then pulled into an autoclave for steam curing;
[0013] (6) Finished product off-line: After the product cured in step (5) is taken out of the autoclave, it is broken into pieces by a breaking machine, and is transported to the finished product yard by a finished product hoist or a forklift and stacked according to specifications to obtain the ultra-lightweight, high-strength and energy-saving building blocks.
[0014] Furthermore, the water content of the slurry in step (1) is 25-28%.
[0015] Furthermore, in step (2), the cement is P·042.5 ordinary silicate cement, the fineness of which is 1.2% after passing through a 0.075 mm sieve; the fineness of the lime is 18.1% after passing through a 0.075 mm sieve; the lime is digested for 14 min at a temperature of 81° C. and has an effective calcium content of 70.84%; the gypsum is desulfurized gypsum from Xingyang Guo Power Plant after desulfurization, and the density of the gypsum is 1.55 kg / m 3 The moisture content is 47.72%, the fineness is through a 0.075mm sieve, and the residue is 3.6%.
[0016] Furthermore, the physical foaming agent in step (2) is protein foaming liquid.
[0017] Furthermore, the chemical foaming agent in step (2) is a mixture of aluminum powder paste and ferrosilicon alloy powder, and the mass ratio of the aluminum powder paste to the ferrosilicon alloy powder is 1:1.
[0018] Furthermore, the aluminum powder paste is a commercially available product, the solid content of the aluminum powder paste is 60%, the fineness is through a 0.075 mm sieve, the sieve residue is 0.1%, and the gasification time of the aluminum powder paste is 15 minutes.
[0019] Furthermore, in the step (3), the temperature of the curing room is 40-60°C, the humidity is 40-80%, and the curing time is 2-4 hours.
[0020] Furthermore, in step (4), the strength of the blank is 0.8-1.2 MPa.
[0021] Furthermore, the cutting in step (4) includes side vertical cutting, groove milling, longitudinal horizontal cutting and transverse cutting.
[0022] Furthermore, the specific steps of steam curing in step (5) are: first slowly heating up for 1h-2h to 120-150°C at a heating rate of 1-2.5°C / min, then rapidly heating up to 170-200°C at a heating rate of 4°C / min, and maintaining the pressure at 170-200°C for 4-6h, at which time the pressure in the autoclave is 0.9-1.2MPa.
[0023] Compared with the prior art, the present invention has the following positive and beneficial effects:
[0024] The present invention uses aluminum powder and ferrosilicon alloy powder as chemical foaming agents to perform chemical foaming: the speed at which silicon ions react with alkaline components in the slurry is slower than that of aluminum. In the composite gasification process, the gasification of ferrosilicon alloy powder and the gasification of aluminum powder are not performed synchronously, the former is slower than the latter, and the ferrosilicon alloy powder is similar to the role of a secondary gasifier. The gasification process of this composite gasification method has unique features: the shape of the pores generated by the gasification of the ferrosilicon alloy powder is regular and accurate, the inner surface is more compact, and the inner surface does not have the lens-shaped cracks that are inevitable on the pore wall of the aluminum powder aerated concrete; when the aluminum powder is used as a single air entraining agent, the pores of the aerated concrete product are relatively simple, and a large number of pores are concentrated in a certain pore size range, and the pores introduced by the ferrosilicon alloy powder interact with the pores generated by the gasification of the aluminum powder, so that the pore size distribution is no longer so simple, and the two pores are cross-linked with each other, so that the pore size distribution in the aerated concrete is more reasonable, and the generated pores are more uniform and smaller, thereby improving the performance of the aerated concrete.
[0025] Due to the complex preparation process of autoclaved aerated concrete, the gas generation environment of aluminum powder and ferrosilicon alloy powder has strict requirements, the thickening rate of the slurry and the gas generation rate of the gas generating agent are difficult to effectively control, resulting in low efficiency of the gas generating agent and a large number of merged pores and connected pores in the pore structure. For ultra-lightweight blocks, as the dosage of the foaming agent increases, the distance between each particle will decrease. When the aluminum particles are gradually converted into expanding bubbles, the distance between the bubbles will decrease, and the bubbles will float upward during the expansion process, thereby increasing the probability of merging between the bubbles, increasing the bubble diameter, and causing the penetration of the holes to cause excessive local porosity, resulting in a decrease in the mechanical properties of the lightweight and high-strength concrete blocks and unstable thermal properties. Since the physical foaming agent protein foaming liquid has a high surface tension, under the preparation method of high-pressure air inflation, the elasticity of the foam is relatively large, the emitted foam has a high stability, and the pore size distribution is relatively uniform. Compared with simple chemical foaming, the present invention adopts a combination of physical foaming and chemical foaming for foaming. Physical foaming and chemical foaming form foam grading, which increases the supporting force between the bubble walls, thereby improving the strength of the concrete block. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a pilot test flow chart of the method for preparing ultra-lightweight, high-strength and energy-saving building blocks of the present invention;
[0027] Figure 2 This is a flow chart of a workshop-scaled experiment of the method for preparing ultra-lightweight, high-strength and energy-saving building blocks of the present invention;
[0028] Figure 3 This is a comparison chart of the compressive strength results of the ultra-lightweight, high-strength and energy-saving building blocks produced in Example 1 of the present invention and the ultra-lightweight, high-strength and energy-saving building blocks produced in Comparative Example 1 and Comparative Example 2;
[0029] Figure 4 This is a comparison chart of thermal conductivity results of the ultra-lightweight, high-strength, energy-saving building blocks produced in Example 1 of the present invention and the ultra-lightweight, high-strength, energy-saving building blocks produced in Comparative Example 1 and Comparative Example 2;
[0030] Figure 5 This is a comparison chart of the compressive strength loss rate of the ultra-lightweight, high-strength and energy-saving building blocks produced in Example 1 of the present invention and the ultra-lightweight, high-strength and energy-saving building blocks produced in Comparative Example 1 and Comparative Example 2;
[0031] Figure 6 It is a comparison diagram of the pore structure and binarization of the ultra-lightweight, high-strength and energy-saving building blocks produced in Example 1 of the present invention and the ultra-lightweight, high-strength and energy-saving building blocks produced in Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0032] The technical scheme of the present invention is further described below in conjunction with specific embodiments. However, it should be understood by those skilled in the art that the following examples are only used to illustrate the present invention and should not be regarded as limiting the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.
[0033] Example 1
[0034] A method for preparing an ultra-lightweight, high-strength, energy-saving building block, the pilot test flow chart and the workshop scale-up test flow chart of the preparation method are as follows: Figure 1 and Figure 2 As shown, the preparation method comprises the following steps:
[0035] (1) Slurry preparation: The weighed fly ash is made into fly ash slurry with a water content of 25-28%, and the fly ash slurry is stored in a slurry tank for standby use;
[0036] (2) Mixing and pouring: Cement, gypsum and ground lime are weighed from each silo tank, mixed with the weighed admixture slurry, the fly ash slurry formed in step (1) and the physical foaming agent protein foaming liquid, and then a weighed mixture of aluminum powder paste and ferrosilicon alloy powder in a mass ratio of 1:1 is added, mixed and poured into a mold. If aerated concrete panels are to be produced, a steel mesh should be placed in the mold in advance. Among them, cement is P.042.5 ordinary silicate cement, the fineness of which is 1.2% after passing through a 0.075 mm sieve; the fineness of lime is 18.1% after passing through a 0.075 mm sieve; the digestion time of lime is 14 min, the digestion temperature is 81° C., and the effective calcium content in lime is 70.84%; the gypsum is desulfurization gypsum used for desulfurization in Xingyang Guodian Power Plant, and the density of gypsum is 1.55 kg / m 3 , the moisture content is 47.72%, the fineness is through 0.075mm sieve, and the sieve residue is 3.6%; the admixture is a special admixture for ash aeration sold on the market, that is, a foam stabilizer, and the foam stabilizer is purchased from Henan Shuoxin New Material Technology Co., Ltd.); the aluminum powder paste is a common commercial product, which was purchased from Suixian Zhuqiao Metal Products Co., Ltd.), the solid content of the aluminum powder paste is 60%, the fineness is through 0.075mm sieve, the sieve residue is 0.1%, and the gasification time of the aluminum powder paste is 15min;
[0037] (3) Curing: The mold cast in step (2) is transferred to a curing room with a temperature of 40-60°C and a humidity of 40-80% for curing for 1.5 h to 3 h to ensure that the slurry completes the thickening and hardening process normally;
[0038] (4) Cutting: After the resting stage, the slurry will harden and form a green body. When the green body reaches 0.8-1.2MPa, it is flipped 90° by the flip hanger and lifted to the cutting machine for side vertical cutting, groove milling, longitudinal horizontal cutting and transverse cutting. At this time, it can be cut according to the designed size to obtain the product of the target size;
[0039] (5) Autoclave curing: The cut green bodies in step (4) are hoisted by a loading crane onto a steam curing trolley for stacking and grouping, and then pulled into an autoclave for steam curing. The specific steps of the autoclave curing are as follows: firstly, the temperature is slowly increased for 1 h to 2 h to 120-150 °C at a heating rate of 1-2.5 °C / min, then the temperature is rapidly increased to 170-200 °C at a heating rate of 4 °C / min, and the pressure is maintained at 170-200 °C for 4-6 h. At this time, the pressure in the autoclave is 0.9-1.2 MPa. The main purpose of strictly controlling the heating rate is to ensure uniform heating inside and outside the green body.
[0040] (6) Finished product off-line: After the product cured by steaming in step (5) comes out of the autoclave, it is broken into pieces by a breaking machine, and transported to the finished product yard by a finished product hoist or a forklift and stacked according to specifications to obtain the ultra-lightweight, high-strength and energy-saving building blocks; wherein the specific amounts of raw materials used to prepare the single-mode building blocks in Example 1 are shown in Table 1.
[0041] Table 1 Specific amounts of raw materials used in single-mode building blocks in Example 1
[0042]
[0043] Comparative Example 1
[0044] A method for preparing an ultra-lightweight, high-strength, energy-saving building block, the steps of the preparation method are exactly the same as those of Example 1, except that in step (2), the physical foaming agent and the chemical foaming agent are replaced by an equal amount of chemical foaming agent aluminum powder paste.
[0045] Comparative Example 2
[0046] A method for preparing an ultra-lightweight, high-strength, energy-saving building block, the steps of the preparation method are exactly the same as those of Example 1, except that in step (2), the physical foaming agent and the chemical foaming agent are replaced by an equal amount of a mixture of aluminum powder paste and ferrosilicon alloy powder in a mass ratio of 1:1.
[0047] Test example
[0048] 1. Pilot test and workshop production scale-up test of ultra-lightweight, high-strength and energy-saving blocks
[0049] The ultra-lightweight, high-strength and energy-saving blocks made of autoclaved aerated concrete products in Example 1, Comparative Example 1 and Comparative Example 2 were subjected to pilot tests and workshop tests, respectively. The specific test results are shown in Table 2 and Table 3, respectively.
[0050] Table 2 Pilot test results of ultra-lightweight, high-strength and energy-saving blocks made of autoclaved aerated concrete in Example 1, Comparative Example 1 and Comparative Example 2
[0051]
[0052]
[0053] After the pilot experiment, three groups of tests were carried out respectively. The first group was the ultra-lightweight, high-strength and energy-saving building blocks prepared in Comparative Example 1 (using chemical foaming agent aluminum powder paste alone), the second group was the ultra-lightweight, high-strength and energy-saving building blocks prepared in Comparative Example 2 (using chemical foaming agent (a mixture of aluminum powder paste and ferrosilicon alloy powder in a mass ratio of 1:1) alone) and the third group was the ultra-lightweight, high-strength and energy-saving building blocks prepared in Example 1 (using chemical foaming agent (a mixture of aluminum powder paste and ferrosilicon alloy powder in a mass ratio of 1:1) It can be seen from the data in Table 2 that the ultra-lightweight, high-strength and energy-saving building blocks made by combining a chemical foaming agent (a mixture of aluminum powder paste and ferrosilicon alloy powder in a mass ratio of 1:1) with a physical foaming agent, protein foaming liquid, have a better effect, and the main performance indicators of strength and thermal conductivity meet the requirements, indicating that the gas generation time is more matched with the slurry thickening time, and the internal pore structure of the finished ultra-lightweight, high-strength and energy-saving building blocks is relatively dense and uniform, and the appearance and various performances meet the national standards.
[0054] Table 3 Workshop test results of ultra-lightweight, high-strength and energy-saving blocks made of autoclaved aerated concrete in Example 1, Comparative Example 1 and Comparative Example 2
[0055]
[0056] In order to verify the readiness of the pilot test results, workshop production scale-up tests were carried out on the above three groups of tests respectively. According to the results of the workshop production scale-up tests, the dry density, compressive strength and thermal conductivity of the ultra-lightweight, high-strength and energy-saving building blocks produced in the third group (using a chemical foaming agent (a mixture of aluminum powder paste and ferrosilicon alloy powder in a mass ratio of 1:1) combined with a physical foaming agent protein foaming liquid) are relatively good, and the antifreeze durability and drying shrinkage of the ultra-lightweight, high-strength and energy-saving building blocks also meet the index requirements; after pilot and workshop scale-up tests, it was further verified that the adaptability of the foaming method combining a chemical foaming agent (a mixture of aluminum powder paste and ferrosilicon alloy powder in a mass ratio of 1:1) with a physical foaming agent protein foaming liquid and the stability of the ultra-lightweight, high-strength and energy-saving building blocks are good and can meet the requirements of continuous production.
[0057] 2. Main performance tests of ultra-lightweight, high-strength and energy-saving blocks
[0058] (1) Compressive strength
[0059] By testing the compressive strength of the ultra-lightweight, high-strength and energy-saving building blocks prepared by the above three groups of different gasification methods, it was found that the compressive strength of the ultra-lightweight, high-strength and energy-saving building blocks prepared by the single gasification method of aluminum powder paste was low, and the compressive strength of the ultra-lightweight, high-strength and energy-saving building blocks prepared by the gasification method of chemical foaming agent (a mixture of aluminum powder paste and ferrosilicon alloy powder in a mass ratio of 1:1) was better than that of the single gasification effect of aluminum powder paste, while the compressive strength of the ultra-lightweight, high-strength and energy-saving building blocks prepared by the gasification method of chemical foaming agent (a mixture of aluminum powder paste and ferrosilicon alloy powder in a mass ratio of 1:1) was better than that of the single gasification effect of aluminum powder paste. The compressive strength of the ultra-lightweight, high-strength and energy-saving building blocks prepared by the gasification method combining a mixture of aluminum powder paste and physical foaming agent protein foaming liquid is better than that of the gasification method using only a chemical foaming agent (a mixture of aluminum powder paste and ferrosilicon alloy powder in a mass ratio of 1:1). This shows that the internal gasification and thickening process of the ultra-lightweight, high-strength and energy-saving building blocks prepared by the composite gasification method combining chemical foaming method and physical foaming method are adapted to the internal gasification and thickening process, the density is high, and the overall compressive strength is high. The specific compressive test results are shown in Figure 3 shown.
[0060] (2) Thermal conductivity
[0061] By testing the thermal conductivity of the ultra-lightweight, high-strength and energy-saving blocks prepared by the above three groups of different gassing methods, the overall experimental results are basically consistent with the compressive strength test results. The thermal conductivity of the ultra-lightweight, high-strength and energy-saving blocks prepared by the composite gassing method combining chemical foaming method + physical foaming method is the smallest, and the thermal conductivity of the ultra-lightweight, high-strength and energy-saving blocks prepared by the chemical gassing method of a single aluminum powder paste is the largest. Thermal conductivity is a key indicator affecting the development of lightweight and high-strength aerated concrete blocks. Through experimental research, it is found that the pore size of the ultra-lightweight, high-strength and energy-saving blocks prepared by the chemical gassing method of a single aluminum powder paste is single, and a large amount of them are concentrated in a certain pore size range, and the particle size is relatively unevenly distributed, which affects the thermal conductivity of the product. The composite gassing method (chemical foaming agent and physical foaming method) can achieve the correlation between different pore sizes and the uniform distribution of pore sizes. The thermal conductivity of the ultra-lightweight, high-strength and energy-saving blocks prepared is low and the thermal conductivity is relatively good. The specific thermal conductivity test results are as follows: Figure 4 shown.
[0062] (3) Compressive strength loss rate
[0063] By conducting antifreeze durability experiments on the above three groups of ultra-lightweight, high-strength and energy-saving building blocks prepared by different gas generation methods, it was found that the antifreeze durability is expressed by the compressive strength loss rate. The smaller the compressive strength loss rate, the better the antifreeze performance of the product and the better the antifreeze durability of the product. The overall law of the product's antifreeze durability is consistent with the change in compressive strength. The ultra-lightweight, high-strength and energy-saving building blocks prepared by chemical gassing of a single aluminum powder paste have low compressive strength, and a large compressive strength loss rate after freeze-thaw. The compressive strength of the ultra-lightweight, high-strength and energy-saving building blocks prepared by chemical gassing using a chemical foaming agent (a mixture of aluminum powder paste and ferrosilicon alloy powder in a mass ratio of 1:1) is improved, and the strength loss rate after freeze-thaw is also relatively small. The ultra-lightweight, high-strength and energy-saving building blocks prepared by a composite gassing method combining a chemical foaming agent (a mixture of aluminum powder paste and ferrosilicon alloy powder in a mass ratio of 1:1) with a physical foaming agent, protein foaming liquid, have good mechanical properties (compressive strength) before freeze-thaw, so the compressive strength loss rate after freeze-thaw is the smallest, and have good antifreeze performance. The specific compressive strength loss rate is as follows: Figure 5 shown.
[0064] (4) Pore structure and binarization
[0065] By comparing the pore structures inside the ultra-lightweight, high-strength and energy-saving building blocks prepared by the above three groups of different gassing methods, it can be seen that the ultra-lightweight, high-strength and energy-saving building blocks prepared by a single gassing method using a chemical foaming agent (aluminum powder paste or a mixture of aluminum powder paste and ferrosilicon alloy powder in a mass ratio of 1:1) cannot achieve cross-linking of multiple pore sizes, and the internal pore size distribution is uneven, and there are some coarse pores, which easily cause stress concentration; while the ultra-lightweight, high-strength and energy-saving building blocks prepared by a composite gassing method using a chemical foaming agent (a mixture of aluminum powder paste and ferrosilicon alloy powder in a mass ratio of 1:1) and a physical foaming agent, protein foaming liquid, have more reasonable pore sizes inside, more uniform and smaller pore sizes, higher pore stability, and more reasonable pore size distribution, which makes the ultra-lightweight, high-strength and energy-saving building blocks have better mechanical properties, antifreeze properties and thermal insulation properties. The specific pore structure and binarization diagram are shown in the following figure. Figure 6 shown.
[0066] Obviously, the above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the invention.
Claims
1. A method for preparing an ultra-lightweight, high-strength, energy-saving building block, characterized in that: The preparation method comprises the following steps: (1) Slurry preparation: The weighed fly ash is made into fly ash slurry with a certain water content, and the fly ash slurry is stored in a slurry tank for standby use; (2) Mixing and pouring: Cement, gypsum and ground lime are weighed from the respective silo tanks, mixed evenly with the weighed admixture slurry, the fly ash slurry obtained in step (1) and the physical foaming agent, and then the weighed chemical foaming agent is added, mixed evenly and poured into a mold; (3) Curing: The mold cast in step (2) is transferred to a curing room with a certain temperature and humidity for curing to ensure that the slurry completes the thickening and hardening process normally; (4) Cutting: After the resting stage, the slurry will harden to form a green body. When the green body reaches a certain strength, it is flipped 90 degrees by a flip hanger and lifted to a cutting machine to cut the green body according to the designed size; (5) Autoclave curing: The green bodies cut in step (4) are hoisted by a loading crane onto a steam curing trolley for stacking and assembly, and then pulled into an autoclave for steam curing; (6) Finished product off-line: After the product cured in step (5) is taken out of the autoclave, it is broken into pieces by a breaking machine, and is transported to the finished product yard by a finished product hoist or a forklift and stacked according to specifications to obtain the ultra-lightweight, high-strength and energy-saving building blocks.
2. The method for preparing an ultra-lightweight, high-strength and energy-saving building block according to claim 1, characterized in that: The water content of the slurry in step (1) is 25-28%.
3. The method for preparing an ultra-lightweight, high-strength and energy-saving building block according to claim 1, characterized in that: In the step (2), the cement is P·042.5 ordinary silicate cement, the fineness of which is 1.2% after passing through a 0.075 mm sieve; the fineness of the lime is 18.1% after passing through a 0.075 mm sieve; the lime has a digestion time of 14 min and a digestion temperature of 81° C. The effective calcium content of the lime is 70.84%; the gypsum is the desulfurized gypsum used for desulfurization in Xingyang Guo Power Plant, and the density of the gypsum is 1.55 kg / m 3 The moisture content is 47.72%, the fineness is through a 0.075mm sieve, and the residue is 3.6%.
4. The method for preparing an ultra-lightweight, high-strength and energy-saving building block according to claim 1, characterized in that: The physical foaming agent in step (2) is protein foaming liquid.
5. The method for preparing an ultra-lightweight, high-strength and energy-saving building block according to claim 1, characterized in that: The chemical foaming agent in step (2) is a mixture of aluminum powder paste and ferrosilicon alloy powder, and the mass ratio of the aluminum powder paste to the ferrosilicon alloy powder is 1:
1.
6. The method for preparing an ultra-lightweight, high-strength and energy-saving building block according to claim 5, characterized in that: The aluminum powder paste is a commercially available product. The solid content of the aluminum powder paste is 60%, the fineness is through a 0.075 mm sieve, the sieve residue is 0.1%, and the gasification time of the aluminum powder paste is 15 minutes.
7. The method for preparing an ultra-lightweight, high-strength and energy-saving building block according to claim 1, characterized in that: In the step (3), the temperature of the curing room is 40-60°C, the humidity is 40-80%, and the curing time is 2-4 hours.
8. The method for preparing an ultra-lightweight, high-strength and energy-saving building block according to claim 1, characterized in that: The strength of the blank in step (4) is 0.8-1.2 MPa.
9. The method for preparing an ultra-lightweight, high-strength and energy-saving building block according to claim 1, characterized in that: The cutting in step (4) includes side vertical cutting, groove milling, longitudinal horizontal cutting and transverse cutting.
10. The method for preparing an ultra-lightweight, high-strength and energy-saving building block according to claim 1, characterized in that: The specific steps of steam curing in step (5) are: first slowly heat up for 1h-2h to 120-150°C at a heating rate of 1-2.5°C / min, then quickly heat up to 170-200°C at a heating rate of 4°C / min, and maintain the pressure at 170-200°C for 4-6h, at which time the pressure in the autoclave is 0.9-1.2MPa.